The emerging roles of inflammasome‐dependent cytokines in cancer development - Van Gorp, Hanne (EMBO Rep, 2019)
In addition to the genomic alterations that occur in malignant cells, the immune system is increasingly appreciated as a critical axis that regulates the rise of neoplasms and the development of primary tumours and metastases. The interaction between inflammatory cell infiltrates and stromal cells in the tumour microenvironment is complex, with inflammation playing both pro‐ and anti‐tumorigenic roles. Inflammasomes are intracellular multi‐protein complexes that act as key signalling hubs of the innate immune system. They respond to cellular stress and trauma by promoting activation of caspase‐1, a protease that induces a pro‐inflammatory cell death mode termed pyroptosis along with the maturation and secretion of the pro‐inflammatory cytokines interleukin (IL)‐1β and IL‐18. Here, we will briefly introduce inflammasome biology with a focus on the dual roles of inflammasome‐produced cytokines in cancer development. Despite emerging insight that inflammasomes may promote and suppress cancer development according to the tumour stage and the tumour microenvironment, much remains to be uncovered. Further exploration of inflammasome biology in tumorigenesis should enable the development of novel immunotherapies for cancer patients.